JURIDICAL ANALYSIS ON THE FAILURE OF VALIDATION AND REGISTRATION OF LIMITED LIBILITY COMPANIES, FOUNDATIONS, AND FIDUCIARY COLLATERAL THROUGH AHU (GENERAL LEGAL ADMINISTRATION) ON LINE SYSTEM - EVI VERONIKA PERANGIN-ANGIN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Dr. Mahmul Siregar, SH, MHum2. Notaris Dr. Suprayitno, SH, MKn3. Dr. T. Keizerina Devi A, SH, CN, MHum AHU (General Legal Administration) by online is a type of legal aid for business people in the process of legal entity validation and registration of fiduciary collateral electronically by Directorate General of AHU of the Ministry of Law and Human Rights. In this case, a Notary’s role is important, and many people who access to AHU Online system become an obstacle in validating legal entity and registering fiduciary collateral which make people, especially Notaries and those who need their service worried.The research used juridical normative method. The main data were secondary data, gathered by conducting library research, and primary data were gathered by conducting interviews. It was expected that this research would achieve its goal, to find out the process of registering limited liability companies, foundations, and fiduciary collateral through AHU online system and its legal consequence and Notaries’ liability for the failure of their registration through AHU online system.The result of the research shows that registering and validating limited liability companies, foundations, and fiduciary collateral through the mechanism of AHU online system begins with the name order and making memorandum of understanding until their validation. Legal consequence of the failure of validation due to online system disorder so that it become expired is that the legal entities will not have legal status and their fiduciary collateral will not have executorial force. A Notary is liable for the failure when there is AHU online system disorder.Keywords: AHU Online, Notary, Limited Liability Company, Foundation, Fiduciary Collateral